THE ORGANIZATION OF ISLAMIC COOPERATION AND THE PROSPECTS OF UZBEKISTAN RELATIONS - Dilafruz Eshankulova Alisherovna (Journals Park Publishing, 2022)
This article discusses the establishment of relations between the Organization of Islamic Cooperation and Uzbekistan, the basis of the organization's activities, mutual agreement and negotiations.
Keywords: IHT, cooperation , Muslim , organization .